ON TWO POSTLARVAL STAGES OF THE SHAD HILSA KELEE (CUVIER) - Bensam, P (Indian Journal of Fisheries, 2011)
Two postlarvae of H. kelee measuring 5.68 mm and 7.92 mm, collectedfrom Gulf of Mannar off Mandapam, are described. In the smaller larva the larvalflnfold was prominent and there were 34 preanal and 9 postanal myomeres. Inthe larger one the flnfoid was almost absent; all the fins except the pelvic hadbeen developed and there were 27 preanal and 16 postanal myomeres. Pigmentationin both the stages was sparse. The differences in features between presentpostlarvae and similar stages of allied clupeids from Indian region are discussed.